The epidemiology of cervical cancer among indigenous women living in Latin America: A systematic review - Iria Riberio Novais; Camila Olegario Coelho; Carla Fabrine Carvalho; Fernanda Surita; Diama Bhadra Vale (Preventive Medicine Reports)
Objective: To review the epidemiological evidence of cervical cancer among Indigenous women living in Latin America. Methods: We conducted a systematic review of the evidence contained in 10 databases spanning 2003–2019. Two reviewers independently compared papers' titles and abstracts against the inclusionary criteria, and a third reviewer resolved discrepancies. Blinded reviewers performed the selection. The articles were organized into the following categories: rates, access, and screening; prevalence of precursor lesions; prevalence and genotypes of Human papillomavirus (HPV); and HPV coinfections. Results: Of the 874 manuscripts we reviewed, 25 were included in the final analysis. We found that cervical cancer is the leading cancer in terms of incidence and mortality among Indigenous women; it presents in advanced stages and is associated with poor survival rates. The prevalence of precursor lesions was higher in women who were geographically isolated. Screening appears to improve outcomes, but women may experience delays in their diagnosis and treatment. Some studies reported populations with a very high prevalence of high-risk Human papillomavirus (hrHPV), and the most frequent genotypes were not different from those of the general population. Chlamydia trachomatis was significantly associated with HPV infection. Conclusions: The data suggested a lack of indicators regarding cervical cancer and its precursor lesions, HPV infection, and cancer indicators. Health policies should target this vulnerable population.